VD_FINDINFO HC / 2011 / 298 vom 10. März 2011 - VD Tribunal cantonal (2011)
RÉSILIATION IMMÉDIATE, DÉLAI DE RÉSILIATION, JUSTE MOTIF, INDEMNITÉEN GÉNÉRAL | 337 CO, 337c CO, 452 al. 2 CPC, 46 LJT, 405 al. 1 CPC (CH)